Principles of virology II - Condit, Richard (Henry Stewart Talks, 2007)
Virus cultivation, Virus isolation, Animal hosts, Cell culture, Recognition of virus infection in culture, CPE: morphological changes, Hemadsorption, Biological assay of viruses, Plaque assay, Focus assay, Endpoint method, Physical assay of viruses, Hemagglutination, Direct particle count, Virus genetics, Genetic principles, Mutation, Engineered host range, Temperature sensitive mutants, Antiviral drugs, Uses of drug resistance/dependence, Recombination and reassortment, Reverse genetics
Archived at 2020/04/29